Investigating Bullying Incidents at SMPN 1 Singosari: A Fascinating Case Study - Nathania, Lintang; Pertiwi, Renita Eka; Fawwazi, Annora Farrel; Simon, Irene Maya; Ratnawati, Ika Anggi; Pratiwi, Awalya Siska (Universitas Negeri Malang, 2024)
School is a place for students to learn, study, and develop character. Every parent hopes that schools would create a more conducive environment for their children to develop into more mature individuals. However, bullying cases in schools are on the rise, causing concern among parents. Bullying has far-reaching consequences, including death. As a result, the researcher wishes to conduct additional research on bullying instances in schools in order to identify bullying behaviour, kinds of bullying behaviour, factors that contribute to bullying, and the impact of bullying on daily activities. The subjects of this study were students of SMPN 1 Singosari. The research method used is a case study with observation and interview techniques. The research results revealed that the types of bullying that occur at SMPN 1 Singosari are physical bullying, verbal bullying, and relational bullying. Family, friendship, and social media influences all contribute to bullying behaviour among the students of SMPN 1 Singosari. The impact that occurs on victims of bullying behavior is that victims become reluctant to socialize or close themselves and even uncomfortable in class to want to leave class as soon as possible.